Aristolochic acid nephropathy - still real danger - Oleszczuk, Rafał; Grzebalska, Agnieszka M.; Kozińska, Iga; Orczykowski, Maciej; Oleszczuk, Anna (Journal of Education, Health and Sport, 2022)
Arystolocholic acid nephropathy is chronic kidney disease caused by the use of substances of natural origin that contain arystolocholic acid. The effects of their use are arystolochic acid nephropathies, which include "Chinese Herbs" nephropathy. The course of the disease is very fast, resulting in progression to end-stage renal disease, and in the future it results in the development of urinary tract cancer. That is why it is so important to recognize it early and start treatment. However, due to disease progression, some patients require dialysis and even kidney transplantation. Although the World Health Organization is trying to stop the spread of the use of harmful substances, there are still reports of this nephropathy appearing in some populations. Despite warnings from the Food and Drug Administration regarding the safety of botanicals containing arystolochic acid and its classification as a human carcinogen, products containing it are still available for purchase online. The purpose of the literature review below is to analyze the latest knowledge on aristolochic acid nephropathy and its associated complication.